Isolation and characterization of dehydrogoniothalamin from Goniothalamus umbrosus - Fasihuddin B, Ahmad,; Laily B Din, Din (PUBLICATIONS & INFORMATION DIRECTORATE, CSIR, 2002)
Three major compounds dehydrogoniothalamin, goniothalamin and 5-acetoxy goniothalamin have been isolated and characterized from the roots of Goniothalamus umbrosus Sinclair. Goniothalamin and 5-acetoxygoniothalamin have been previously reported from several Goniothalamus sp. However, dehydrogoniothalamin has not been reported so far.